Analisis Faktor-Faktor Sosial Dalam Bullying: Perspektif Pendidikan Anti-Bullying Melalui Lensa Filsafat Ibnu Khaldun: DOI 10.58569/jies.v2i2.750 - Firnando, Hero Gefthi (Pascasarjana Universitas Islam Jakarta, 2024)
This research aims to analyze social factors in bullying using an anti-bullying education approach through the philosophical lens of Ibn Khaldun. The research method employs literature analysis and a review of existing studies to identify and comprehend the dynamics of social factors related to the phenomenon of bullying. The research objective is to provide a robust conceptual foundation for the development of anti-bullying education strategies. The literature analysis highlights the roles of social solidarity, cultural change, and inequality as key factors in bullying incidents. Ibn Khaldun's contributions to this perspective offer a philosophical insight that enriches prevention and intervention approaches. The implications of these findings support the formulation of policies and educational practices in anti-bullying that are more effective in responding to evolving social dynamics.